A novel methodology to study nanoporous alumina by small‐angle neutron scattering. Issue 4 (28th June 2019) - Christoulaki, Anastasia; Chennevière, Alexis; Grillo, Isabelle; Porcar, Lionel; Dubois, Emmanuelle; Jouault, Nicolas
Abstract : This work reports a novel methodology to extract quantitative information from small‐angle neutron scattering measurements of nanoporous alumina. Abstract : Nanoporous anodic aluminium oxide (AAO) membranes are promising host systems for confinement of condensed matter. Characterizing their structure and composition is thus of primary importance for studying the behavior of confined objects. Here a novel methodology to extract quantitative information on the structure and composition of well defined AAO membranes by combining small‐angle neutron scattering (SANS) measurements and scanning electron microscopy (SEM) imaging is reported. In particular, (i) information about the pore hexagonal arrangement is extracted from SEM analysis, (ii) the best SANS experimental conditions to perform reliable measurements are determined and (iii) a detailed fitting method is proposed, in which the probed length in the fitting model is a critical parameter related to the longitudinal pore ordering. Finally, to validate this strategy, it is applied to characterize AAOs prepared under different conditions and it is shown that the experimental SANS data can be fully reproduced by a core/shell model, indicating the existence of a contaminated shell. This original approach, based on a detailed and complete description of the SANS data, can be applied to a variety of confining media and will allow the further investigation of condensed matter under confinement.